1979
DOI: 10.1530/jrf.0.0570137
|View full text |Cite
|
Sign up to set email alerts
|

Exchange of krypton-85 between the blood vessels of the human uterine adnexa

Abstract: Summary. A miniature Geiger\p=n-\M\l=u"\llerprobe was inserted into one ovary of 8 women undergoing hysterectomy. A control probe was inserted into the other ovary of 2 of the women. Krypton-85 in 0\m=.\15 m-NaCl was infused into the adjacent utero-ovarian vein and the radioactivity was registered for 5\p=n-\14min after the infusion. An increase of radioactivity was recorded in the ovary in 5 cases. In one of the women with 2 probes, no increase in radioactivity was observed in the control ovary. The results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1981
1981
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…The experimental results of Caldwell & Moor (1971), Ginther & Bisgard (1972), Goding (1974), Hixon & Hansel (1974) and Land, Baird & Scaramuzzi (1976) have supported this suggestion and similar evidence of utero-ovarian local transfer of prostaglandin in the pig has been given by Gleeson (1974), Lindloff, Holtz, Elsaesser, Kreikenbaum & Smidt (1976), Krzymowski, Kotwica, Okrasa, Doboszynska & Ziçcik (1978) and Kotwica (1980). Study of the local transfer of inert radioactive gases (Einer-Jensen, 1974;Einer-Jensen & McCracken, 1977;Bendz, Einer-Jensen, Lundgren & Janson, 1979) has shown that xenon-133 or krypton-85 infused into the uterine horn of the mouse, hamster and guinea-pig or into the utero-ovarian vein of sheep or women reached higher concentrations in the adjacent than in the opposite ovary. A counter-current transfer of hormone in the ovarian pedicle has been described for progesterone in sheep (McCracken & Einer-Jensen, 1976;Walsh, Yutrzenka & Davis, 1979), and for testosterone for sows (Krzymowski, Kotwica & Stefariczyk, 1979) and a local steroidconcentrating mechanism in the female reproductive vasculature seems likely.…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…The experimental results of Caldwell & Moor (1971), Ginther & Bisgard (1972), Goding (1974), Hixon & Hansel (1974) and Land, Baird & Scaramuzzi (1976) have supported this suggestion and similar evidence of utero-ovarian local transfer of prostaglandin in the pig has been given by Gleeson (1974), Lindloff, Holtz, Elsaesser, Kreikenbaum & Smidt (1976), Krzymowski, Kotwica, Okrasa, Doboszynska & Ziçcik (1978) and Kotwica (1980). Study of the local transfer of inert radioactive gases (Einer-Jensen, 1974;Einer-Jensen & McCracken, 1977;Bendz, Einer-Jensen, Lundgren & Janson, 1979) has shown that xenon-133 or krypton-85 infused into the uterine horn of the mouse, hamster and guinea-pig or into the utero-ovarian vein of sheep or women reached higher concentrations in the adjacent than in the opposite ovary. A counter-current transfer of hormone in the ovarian pedicle has been described for progesterone in sheep (McCracken & Einer-Jensen, 1976;Walsh, Yutrzenka & Davis, 1979), and for testosterone for sows (Krzymowski, Kotwica & Stefariczyk, 1979) and a local steroidconcentrating mechanism in the female reproductive vasculature seems likely.…”
Section: Introductionmentioning
confidence: 54%
“…The mechanism of this pathway is unknown. Bendz et al (1979) have suggested that the transfer of krypton-85 in women is based on passive diffusion aided by the close relationship between the ovary vein and the tortuous artery. In sows, extensive surface contact between the ovarian vein and artery would aid direct passage of testosterone, but we suggest that more than direct diffusion is involved because although the radioactivity in arterial blood decreased, it continued to appear in the ovarian artery 10 min after the infusion was stopped.…”
Section: Discussionmentioning
confidence: 99%
“…If a drug that would inhibit the follicular synthesis or ovulatory action of prostaglandins could be delivered to the ovary via a local mechanism, a problem such as the one described above might be circumvented. An intrauterine delivery system may be a possible approach, especially since a direct vascular relationship exists between the uterus and ovaries of a number of species (Ginther, 1974), including man (Bendz, Einer-Jensen, Lundgren & Janson, 1979). Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Estradiol increases blood flow in ovarian, uterine, and in systemic arteries. 23 The ovarian steroids reach, because of the local transfer mechanisms, 5,6,24 concentrations in the ovarian artery and tubal arterial arcade that exceed those measured in systemic circulation. Accordingly, we recently have demonstrated that in cycling women serum levels in ovarian steroids are significantly higher in periuterine vessels than in systemic vessels, 25 thus confirming the existence of mechanisms of local distribution of ovarian hormones to the internal reproductive apparatus.…”
Section: Regulation Of Uterine Blood Supplymentioning
confidence: 99%